The Influence of Leadership Style and Work Stress on Employee Job Satisfaction - Yessi Yunita; Deni Budiana (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Leadership style is a set of characteristics used by leaders to influence subordinates so that organizational goals can be achieved. Job stress is a feeling of pressure experienced by employees in dealing with work. Job Satisfaction A person's attitude towards his work can be a positive or negative attitude, satisfied or dissatisfied. This study aims to determine how much influence the leadership and job stress on employee job satisfaction in the sales division of PT Cipta Wahana Sentosa. The research method used is a quantitative method with a descriptive and verification approach. The number of respondents in this study was 78 employees of the sales division of PT Cipta Wahana Sentosa. Analysis of the data used is path analysis which is processed using SPSS version 26. Based on the results of the study, it can be concluded that leadership style partially affects job satisfaction by 75,8% and job stress affects job satisfaction by 6,5%, while simultaneously style leadership and job stress affect job satisfaction by 82,3%.